(untitled) (Italian Journal of Public Health, 2008)
Background: The following article focuses on nutrition related topics that had been implemented in the curricula of secondary level schools in Saxony, Germany, during their reorganisation. The overall aim was to make children and adolescents more sensitive to nutrition related topics in their daily lives. Thus, the lesson plans that have been created for the teachers will be introduced and a preview of further steps will be given. Methods: For the subject economics-technology-household exemplary lesson plans within the framework of the Saxon curricula were created for secondary level schools from grades eight to ten. Furthermore, conceptions for project days and different kinds of courses were prepared for nutrition related topics. After the lesson plans were tested and three teachers were consulted, feedback from all of the subject teachers was obtained via interview for qualitative analysis. Fifty-two pupils were asked to answer a questionnaire. The responses according to the lessons were taken partially standardised and were evaluated. Results: Teachers as well as pupils appreciated the complex lesson plans and materials on scientific basis.The consulted subject teachers emphasised that the lesson plans can be regarded as a fundamental preparation for their further work. If necessary they need to be adapted to the teacher’s ideas and special circumstances in school. Conclusions: With the preparation of the lesson plans important steps were realised within the restructuring process of Saxon curricula. Thus, the implementation of nutrition related topics in school curricula could be achieved.